1995
DOI: 10.2466/pr0.1995.76.3.847
|View full text |Cite
|
Sign up to set email alerts
|

Place Attachment, Isolation, and the Power of a Window in a Hospital Environment: A Case Study

Abstract: This paper describes the relevance of the literature on environmental psychology to the coping strategies a leukemia patient used in adapting to psychological and physical isolation on a hospital bone marrow transplant unit and oncology unit. The case study describes the difficulty of place attachment on the isolation unit and its evolution on the oncology unit. The power of a window with a natural view--including a view of a cemetery--was especially evident even as the disease became terminal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The presence of natural light, which is facilitated by the presence of windows, has also been shown to aid in recovery following spinal surgery (Walch et al, 2005). Along related lines, Baird and Bell (1995) report an interesting case in which an isolated leukemia patient became more attached to a room that overlooked the cemetery she would eventually be buried in, because it contained a stand of trees that was more natural than the alternatively available view. Moore (1981) reported data indicating that prisoners who resided in cells overlooking an open field required fewer visits to the infirmary when compared with prisoners residing in cells without the natural view, and Heerwagen (1990) found that visual access to natural murals reduced anxiety and blood pressure in dental patients.…”
Section: Visual Access To Natural Environmentsmentioning
confidence: 99%
“…The presence of natural light, which is facilitated by the presence of windows, has also been shown to aid in recovery following spinal surgery (Walch et al, 2005). Along related lines, Baird and Bell (1995) report an interesting case in which an isolated leukemia patient became more attached to a room that overlooked the cemetery she would eventually be buried in, because it contained a stand of trees that was more natural than the alternatively available view. Moore (1981) reported data indicating that prisoners who resided in cells overlooking an open field required fewer visits to the infirmary when compared with prisoners residing in cells without the natural view, and Heerwagen (1990) found that visual access to natural murals reduced anxiety and blood pressure in dental patients.…”
Section: Visual Access To Natural Environmentsmentioning
confidence: 99%
“…Loneliness may involve monotony, boredom, sadness and claustrophobia; wandering of thoughts; lack stimulation, comprehension and people to talk to; fear of abandonment; and loss of touch with the outside world (Holland et al . ; Baird & Bell ; Oldman‐Pritchard ). Being isolated can also make patients feel imprisoned, since they may lose their freedom and their control over their lives (Thain & Gibbon ).…”
Section: Discussionmentioning
confidence: 99%